Hospitalised poisonings in Australian children: a 10-year retrospective study. (4th March 2023) - Arbaeen, Abrar; Noghrehchi, Firouzeh; Wheate, Nial J.; Cairns, Rose
Abstract: Introduction: Paediatric poisoning is a major cause of childhood injury, and most poisonings are preventable. We aimed to describe hospitalisations resulting from poisoning and envenomation in Australian children, including demographics, cause of the exposure, hospital length of stay, rates of intensive care unit admission and in-hospital deaths. We also aimed to describe risk factors for increased length of stay and intensive care unit admission. Methods: A retrospective analysis was performed of hospitalised poisoning and envenomation cases of children (<15 years) in Australia from 1 July 2009 to 30 June 2019. A nationwide hospital admissions database was used for this study. Results: During the 10-year study period 33, 438 children were admitted to hospital due to a pharmaceutical or non-pharmaceutical poisoning/envenomation; an average of 74.8 cases per 100, 000 population per year. Approximately 10 children were admitted to hospital each day for poisoning. Over 70% of these cases were due to pharmaceuticals ( n = 23, 628), most frequently non-opioid analgesics, anti-pyretics and anti-rheumatics ( n = 8759, 37.1% of pharmaceutical exposures). The most common non-pharmaceutical exposure was contact with venomous animals and toxic plants ( n = 4578, 46.7% of non-pharmaceuticals). Intentional self-harm occurred in 7833 (23.4%) of cases. Intensive care unit admission was required in 519 cases (2.5% of the 20, 739 cases where this information was available), while 200 (0.96% of 20, 739) needed ventilator support. Ten children (0.03%) died. Older age, female sex, poisoning with pharmaceuticals and metropolitan hospital location were associated with increased length of stay. Older age and poisoning with pharmaceuticals were also associated with intensive care unit admission. Conclusion: Approximately 10 children were admitted to hospital with poisoning every day in Australia. Most poisonings were due to pharmaceuticals, particularly simple analgesics that are found in most Australian homes. Severe outcomes (intensive care unit admissions and deaths) were rare.